Observations of Magnetic Domain Structure Change in Nd2Fe14B Magnets at Elevated Temperature with External Magnetic Field by Lorentz Microscopy. Issue 1754 (9th June 2015) - Suzuki, Toshimasa; Kawahara, Koichi; Tanaka, Haruka; Ozaki, Kimihiro
ABSTRACT: In this study, we conducted the in-situ observations of the magnetic domain structure change in Nd2 Fe14 B magnets at elevated temperature by transmission electron microscopy (TEM) / Lorentz microscopy. The in-situ observations in Nd2 Fe14 B magnets revealed that the magnetization reversal easily occurred at the elevated temperature. At more than 180°C, the magnetic domain wall motion could be observed by applying the magnetic field of less than 20 mT. The motion of the magnetic domain wall was discontinuous and the domain wall jumped to one grain boundary to the neighboring grain boundary at 180°C. On the other hand, the continuous domain wall motion within grain interior as well as discontinuous domain wall motion was observed at 225°C, and some grain boundaries showed still strong pinning effect even at 225°C. The temperature dependence of the pinning effect of grain boundaries would not uniform.